Onion anthocyanins: Extraction, stability, bioavailability, dietary effect, and health implications - Samota, Mahesh Kumar; Sharma, Madhvi; Kaur, Kulwinder; Sarita,; Yadav, Dinesh Kumar; Pandey, Abhay K.; Tak, Yamini; Rawat, Mandeep; Thakur, Julie; Rani, Heena (Frontiers in Nutrition, 2022)
Anthocyanins are high-value compounds, and their use as functional foods and their natural colorant have potential health benefits. Anthocyanins seem to possess antioxidant properties, which help prevent neuronal diseases and thereby exhibit anti-inflammatory, chemotherapeutic, cardioprotective, hepatoprotective, and neuroprotective activities. They also show different therapeutic effects against various chronic diseases. Anthocyanins are present in high concentrations in onion. In recent years, although both conventional and improved methods have been used for extraction of anthocyanins, nowadays, improved methods are of great importance because of their higher yield and stability of anthocyanins. In this review, we compile anthocyanins and their derivatives found in onion and the factors affecting their stability. We also analyze different extraction techniques of anthocyanins. From this point of view, it is very important to be precisely aware of the impact that each parameter has on the stability and subsequently potentiate its bioavailability or beneficial health effects. We present up-to-date information on bioavailability, dietary effects, and health implications of anthocyanins such as antioxidant, antidiabetic, anticancerous, antiobesity, cardioprotective, and hepatoprotective activities.